Pengaruh bahan ajar IPA tema kesehatan pernapasan dan ekskresi manusia mengintegrasikan keterampilan belajar terhadap kompetensi siswa kelas VIII di SMPN 7 Padang - winni suhadi; Asrizal Asrizal; Yohandri yohandri; Wahyuni Satria Dewi (Universitas Negeri Padang, 2019)
Science teaching should be done in an integrated pattern according to the demands of the 2013 curriculum. Physics, Chemistry, and Biology materials were integrated into a discussion of the science. Science. In the 21st century the curriculum development of science need to be done to improve soft skills and hard skills of students. The government has demanded to improve student learning outcomes by integrating learning skills and integrated science teaching in junior high school. However, the real condition indicated science that teachers were still having difficulty in implementing integration of the physics, chemistry and biology learning material in science teaching. This can be seen from the average value of knowledge test result of students was 40.91 and this average value can be grouped into low category. The solution to solve of this problem was to apply science learning material on the our respiratory and the excretory theme by integrating learning skills to improve student competence. The purpose of this research was to investigate the effect of science learning material on the our respiratory and the excretory theme by integrating learning skills on the competencies of VIII grade students in SMP N 7 Padang. This type of research was posttest-only control designed. The research population was all eight grade students in SMPN 7 Padang. The sampling technique used cluster random sampling. The research instruments consisted of an observation sheet for attitude aspect, written test for knowledge aspect, and performance assessment sheet for skills aspect. The data which obtained were analyzed by using descriptive statistics and comparison of two means test. The result of the hypothesis test stated that there was a difference in the competence between students who used the integrated science teaching material with learning skills on the theme of respiratory and excretory theme with students who didn’t use in aspects of knowledge, attitude, and skills. This indicated that the use of integrated science learning material with learning skills on respiratory and excretory theme has given a significant effect on the competence of VIII grade students in SMPN 7 Padang.